O uso das tic no processo de ensino-aprendizagem na proposta pbl: estudo de caso com alunos de medicina - Lopes, Elys Gardênia de Freitas (2018)
Information and Communication Technologies are present in all areas, specifically in education, contributing to the emergence of active teaching methodologies. As an example of these methodologies, we can highlight in this work Problem-Based Learning (PBL), which is a teaching method that alters the perspective of how the teaching-learning process occurs, bringing to the student the role of protagonist and for the teacher the facilitator. The application of this methodology employs the use of problems as a mechanism to stimulate learning and as a way to develop the skills. Therefore, students learn while interacting in solving a proposed problem. The dynamics of PBL implementation make it possible to formulate the proposed problems using a variety of sources, such as through Virtual Learning Environments (VLE). In this sense, the objective of this work is to analyze, in the pedagogical context, the teaching-learning process produced through the simultaneous use of the computational tool Problem and the PBL methodology. This combination allows the development of educational practices focused on the synchronous application of theory and practice. The use of this tool aims to assist the facilitator and the students in the implementation of the PBL in VLE Moodle. The methodology used is based on the use of the cycle of execution of Problem-Based Learning, applied through the computational tool Problem, in the modality of distance education. As for the research methods, qualitative and quantitative procedures were used, and the case study and descriptive statisTIC were methodologically applied, respectively. The methodological foundations of the research are supported by the criteria of Barrows (2006), Hmelo-Silver (2006), Moran (2018) and the formulation of two hypotheses proposed by Correa (2003). As a result of the research, it was possible to use a PBL support module integrated with Moodle, in order to meet the main goals related to the greeting of the cycle of application of this methodology, as well as to help students and facilitators during the teaching-learning process